2019
DOI: 10.1055/s-0039-3402079
|View full text |Cite
|
Sign up to set email alerts
|

Gait Analysis 1 Year after Primary TKA: No Difference between Gap Balancing and Measured Resection Technique

Abstract: Mechanical alignment in total knee arthroplasty (TKA) can be achieved using dependent bone cuts. The hypothesis is that patients have a better balanced TKA, as a result. The aim of this study was to determine if this technique is superior to an independent bone cut technique in terms of gait parameters, patient-reported outcome measures (PROMs), and satisfaction assessed before surgery and at 1-year follow-up. A total of 58 patients were evaluated before and 1 year following TKA, using the Press Fit Condylar (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The frequency of condylar lift‐off, PCS, MCS, KSS and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores were comparable between the groups at 1 year post‐surgery. In a clinical trial of 58 patients using a posterior‐stabilized Press Fit Condylar (PFC) Sigma TKA system (Depuy Orthopaedics, Inc., Warsaw, IN), Miozzari et al [20] found no significant differences between the measured resection and gap balancing groups at 1 year follow‐up. In addition, the authors performed 3D gait evaluation and found no differences between the groups in gait parameters including gait velocity and flexion range in the gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of condylar lift‐off, PCS, MCS, KSS and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores were comparable between the groups at 1 year post‐surgery. In a clinical trial of 58 patients using a posterior‐stabilized Press Fit Condylar (PFC) Sigma TKA system (Depuy Orthopaedics, Inc., Warsaw, IN), Miozzari et al [20] found no significant differences between the measured resection and gap balancing groups at 1 year follow‐up. In addition, the authors performed 3D gait evaluation and found no differences between the groups in gait parameters including gait velocity and flexion range in the gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Miozzari et al, 2021 demonstrated no significant difference between the gap balancing and measured resection groups in terms of gait analysis parameters, WOMAC scores, or SF-12 scores. 15 The agreement of no difference between these independent validation tools further points toward the potential use of gait analysis in A recent article that demonstrated strong evidence for patientspecific instrumentation did not corroborate the validity of gait analysis. 17 Though functional (p < 0.05) and radiographic differences (p < 0.05) were noted in this study between the patients with custom femoral and tibial bone blocks, no clinical or gait analysis parameters were statistically significant.…”
Section: Studying Surgical Techniquesmentioning
confidence: 99%
“…Five of the screened articles used gait analysis as an outcome measure in studies comparing surgical techniques. Two of these articles included a pre-operative and post-operative gait analysis, 15,16 and three of them included only a post-operative gait analysis. 17,18 Miozzari et al, 2021 demonstrated no significant difference between the gap balancing and measured resection groups in terms of gait analysis parameters, WOMAC scores, or SF-12 scores.…”
Section: Studying Surgical Techniquesmentioning
confidence: 99%
“…However, there is no single method that results in general patient satisfaction. Miozzari et al 12 compare gap balancing and measured resection showing that these two methods lead to the same outcomes. In a study by Nakajima et al 13 , patient-reported outcomes have been in favor of kinematically aligned implants against measured resection technique.…”
Section: Introductionmentioning
confidence: 99%